Clients of Female Sex Workers: A Population-Based Survey of China - Pan, Suiming (Oxford University Press, 2011)
The control of HIV and other sexually transmitted infections (STI) is a challenge in China, with female sex workers (FSW) and male clients suspected as bridge groups. This study used a 2006 national probability survey of 2,707 adult men. Among men 15–49 years old, the prevalence of FSW contacts last year was 4.2% (95% CI, 3.3–5.2) overall, with 7.2% (CI, 5.9–8.7) in urban and 1.8% (CI, 1.0–3.3) in rural areas. In urban areas, the men most at risk for FSW were high income, often traveled, engaged in business entertaining, ages 25–39, and had early sex histories. When compared to men with only wife or stable sex partner, those most likely to report STI last year also reported FSW sex of any type (aOR,13.10; CI, 5.87–29.42). Additionally, when compared to men reporting consistent condom use with FSW, men with inconsistent condom use had elevated STI (aOR, 3.71; CI, 1.18–11.66). Additional efforts are needed for high income men in urban areas, and on consistent condom use with FSW.